EFEKTIVITAS KEBIJAKAN INVENTARISASI DAN DOKUMENTASI KARYA CIPTA KEBUDAYAAN DI SULAWESI SELATAN - Makkawaru, Zulkisli; Tira, Andi (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Regulation and national policy on intellectual property in order to get around the fact offoreign claims were in the melee. Command of the Act to conduct an inventory movementand the intellectual work of kumunal logging need to be examined in the field. Thisresearch takes place in Bulukumba, Wajo, Makassar, and Toraja. The method used wasqualitative empirical with doctrinal issues the question form and conduct interviews andreview of the literature/secondary data. The results obtained that the intellectual work ofcommunal inventory has not been effectively carried out by the local authorities in SouthSulawesi.